Air Bubble Bridge‐Based Bioinspired Underwater Adhesion (Small 42/2021). Issue 42 (21st October 2021) - Wang, Yan; Zhang, Liwen; Guo, Yurun; Gan, Yang; Liu, Guang; Zhang, Deyuan; Chen, Huawei
Abstract : Underwater Adhesion In article number 2103423, Huawei Chen and co‐workers propose a novel concept of underwater adhesion inspired by the diving beetle, which utilizes air bubbles as an adhesive to realize nondestructive and repeatable adhesion working across a wide range of scales. The bubble acting forces can be adjusted and controlled by spine structures and surface wettability. These findings enrich the underwater adhesion strategy and provide potential solutions for the fields of chemical, medical and mechanical engineering.